Unraveling the Correlations between Mechanical Properties, Miscibility, and Film Microstructure in All‐Polymer Photovoltaic Cells. (6th May 2022) - Zhou, Kangkang; Xian, Kaihu; Qi, Qingchun; Gao, Mengyuan; Peng, Zhongxiang; Liu, Junwei; Liu, Yang; Li, Saimeng; Zhang, Youdi; Geng, Yanhou; Ye, Long
Abstract: The rapid development of low bandgap polymer acceptors has promoted the efficiency up to ≈17% for all‐polymer solar cells (all‐PSCs). Nevertheless, the polymeric blend film, core to the photoelectric conversion of all‐PSCs, has not been thoroughly understood in terms of the influence and regulatory factors of mechanical properties, which hinders the advances in flexible and wearable applications. Herein, a range of characterization methods is combined to investigate the mechanical properties, miscibility, and film microstructure of the blends based on several representative polymer donors (PTzBI‐Si, PTVT‐T, PM6 and PTQ10) and a benchmark polymer acceptor N2200, and to further reveal the miscibility‐property relationships of the miscibility property. The results stress that fracture behaviors and elastic moduli of these blends with varied compositions show different changing trends, which are affected by molecular interactions and aggregated structure of the blends. The elastic moduli of the four all‐polymer blends can be nicely predicted by different models that are deduced from macromolecular mechanics. Most crucially, the correlations between elastic modulus, morphology, and miscibility of all‐polymer blends are elucidated for the first time. The derived relationships is validated with another high‐efficiency blend and will be the key to the successful fabrication of mechanically robust and stretchable all‐PSCs with high efficiency. Abstract : The key mechanical properties of five all‐polymer photovoltaic blend films are determined with a set of complementary characterization methods. The composition dependences of the film stretchability and elastic moduli of these all‐polymer blends with different miscibility are well elucidated. Notably, the elastic moduli of these all‐polymer blend films with various morphologies can be predicted by mechanical models for the first time.